THERAPEUTIC APPLICATION OF A SIDDHA FORMULATION PATAIC CANKARAN - A REVIEW - M, Navinkumar; G, Nivetha; Radha P,; Mohideen M, Ahamed (International Journal of Ayurveda and Pharma Research, 2019)
Padarthamarai is the fungal skin infections and are categorised under Kutta Rogam (Padarthamarai -Pundareega Kutam). Many siddha drugs are prescribed for these diseases among them, Pataic Cankãran is exclusively mentioned for these disease as an internal and external medicine in Siddha literature - Siddha Vaidya Thirattu. Two different preparations are mentioned under Pataic Cankãran and differences observed in the ingredients as in Pataic Cankãran I Ankol (Alangium salvifolium (L.f.) Wang.), Marukkarai (Catunaregam spinosa (Thunb.) Tirvengadumia) and Elumitchai (Citrus aurantifolia (Christm.) Swingle), where as in Pataic Cankãran II, Thagarai (Senna tora (L.) Roxb.), Erruku (Calotropis procera (Ait.) R.Br.) are used. Even though Pataic Cankãran is mentioned in literature exclusively for dermatophytosis which is no longer in uses; Clinical study and standardisation of this drug have not been done so far, but In-vitro anti-dermatophytotic activities of the individual ingredient of these formulations have already been proved. The present review article aimed to document the biological, pharmacological and therapeutic applications such as anti-microbial, anti-bacterial and anti-inflammatory activities of individual ingredients used in Pataic Cankãran I with reference to skin diseases. This study will help to understand the need of research study on this ancient Siddha formulation.